Determinants of Marketable Surplus of African Bush Mango Kernel (Ogbono) in Kolokuma/Opokuma Local Government Area of Bayelsa State, Nigeria - Okuduwor A. A; Tuaneh G. L; Isikima T; Jimmy P. S (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study evaluated the determinants of marketable surplus of African Bush Mango Kernels (Irvingia gabonensis) (ogbono) in Kolokuma/Opokuma Local Government Area of Bayelsa State. Multi-stage saying was used to select a total of 60 respondents for the study. The data used for the study was collected using a well-structured questionnaire. The data collected was analysed using descriptive statistics and multiple regression. The results showed that ogbono in the study area is male dominated business (53.3%), majority of the producers (48.3%) were married, and 53.3% had a household size of 6-10 persons. The coefficient of multiple determination (R2) was 0.959, the quantity of ogbono produced, age of producers, quantity of ogbono for household consumption was significant at p<0.01, p<0.5 and p<0.01 respectively and positively influenced the quantity of ogbono sold. The 5quantity of ogbono given as gift was negative and significant at p <0.01. The study concluded that ogbono production in the study area is viable and it was recommended that Government support, improved processing and storage facilities should be provided.